Older people with severe loneliness have an atrophied thalamus, hippocampus, and entorhinal cortex. (16th November 2022) - Imai, Ayu; Matsuoka, Teruyuki; Narumoto, Jin
Abstract: Objectives: Loneliness has been shown to increase the risk of dementia. However, it is unclear why greater loneliness is associated with greater susceptibility to dementia. Herein, we aimed to examine the morphological characteristics of the brain associated with loneliness in older people concerned about cognitive dysfunction. Methods: In this retrospective study, 110 participants (80 with amnestic mild cognitive impairment, and 30 cognitively healthy individuals) were included. Participants were assessed using the revised University of California at Los Angeles (UCLA) loneliness scale and had undergone magnetic resonance imaging. Spearman correlation analysis and Mann–Whitney U tests were used to examine the clinical factors associated with loneliness. Multiple regression was performed to examine the relationship between the revised UCLA loneliness scale score and regional gray matter (GM) volume on voxel‐based morphometry. Results: The revised UCLA loneliness scale scores were not significantly correlated with age, sex, or mini‐mental state examination (MMSE) scores. Multiple regression using age, sex, MMSE score, and total brain volume as covariates showed negative correlations of the revised UCLA loneliness scale scores with the grey matter volume in regions centered on the bilateral thalamus, left hippocampus and left parahippocampal gyrus, and left entorhinal area. Conclusions: Subjective loneliness was associated with decreased GM volume in the bilateral thalamus, left hippocampus, and left entorhinal cortex of the brain in the older people, thereby providing a morphological basis for the increased risk of dementia associated with greater loneliness. Key points: The morphological features of the brain related to loneliness were examined in older patients with concerns about cognitive dysfunction. The severity of loneliness was associated with reduced grey matter volume in the bilateral thalamus, left hippocampus, and entorhinal cortex of older people. Morphological evidence showed that greater loneliness might be associated with an increased risk of dementia.